The Effect of Brand Image, Product Diversity, Online Trust, Security on Repurchase Interest at The Shopee Marketplace in Jakarta - Ayatollah Arsy Amirarasy; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of brand image, product diversity, online trust, security on repurchase interest at the Shopee marketplace in Jakarta. The population in this study used a purposive sampling technique where the population taken was 100 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that Brand Image had a positive and significant effect on repurchase interest in the Shopee market place. Product diversity has a positive and significant effect on repurchase interest in the Shopee market place. Online Trust has a positive and significant effect on repurchase interest in the Shopee market place. Product diversity has a positive and significant effect on repurchase interest in the Shopee market place. Based on the results of the regression, it was found that product diversity had the highest contribution value to buying interest in this study.